Recurrent circuitry sustains Drosophila courtship drive while priming itself for satiety - Zhang, Stephen X. (Curr Biol, 2019)
Motivations intensify over hours or days, promoting goals that are achieved in minutes or hours, causing satiety that persists for hours or days. Here we develop Drosophila courtship as a system to study these long-timescale motivational dynamics. We identify two neuronal populations engaged in a recurrent excitation loop, the output of which elevates a dopamine signal that increases the propensity to court. Electrical activity within the recurrent loop accrues with abstinence and, through the activity-dependent transcription factor CREB2, drives the production of activity-suppressing potassium channels. Loop activity is decremented by each mating to reduce subsequent courtship drive, and the inhibitory loop environment established by CREB2 during high motivation slows the reaccumulation of activity for days. Computational modeling reproduces these behavioral and physiological dynamics, generating predictions that we validate experimentally and illustrating a causal link between the motivation that drives behavior and the satiety that endures after goal achievement.